PENGARUH PENDELEGASIAN WEWENANG DAN BIROKRASI TERHADAP KEPUASAN KERJA PEGAWAI RSUD (SURVEY PADA RUMAH SAKIT UMUM DAERAH KABUPATEN CIREBON, KOTA CIREBON, KABUPATEN INDRAMAYU,DAN KABUPATEN KUNINGAN) - Heriyono, Heriyono (Exchall, 2021)
The background of this research is based on the phenomenon that local government-owned hospitals, the focus is on serving the community in the field of Health, so, chasing profit is not the top priority for hospitals, as a result sometimes slow service, facilities, and administration are also slow. This study aims to analyze the influence of Delegation of Authority, and Bureaucracy, on The Job Satisfaction of Employees of Regional Public Hospitals, both simultaneously and partially. This study describes causal (causal) relationships between variables and tests research hypotheses. Data determination techniques are done by probability sampling technique. Analysis method using SEM (StructureEquation Modelling). The results of the study obtained that there is a significant influence of delegation of authority and bureaucracy terhadap kepuasan kerja Employees by 66,89 %. There is a positive and significant influence, either directly or indirectly from the Delegation of Authority to employee job satisfaction (39,57 %), and bureaucracy to employee job satisfaction (27,32%) Keyword : Division of Work, Delegation of Authority, Bureaucracy, Officer Job Satisfaction, and Officer Performance